Identifying Conservative Interventions for Individuals with Subacromial Pain Syndrome Prior to Undergoing a Subacromial Decompression: A Scoping Review - Joseph A Signorino; Aubrey G. Thompson; Benjamin R Hando; Jodi L Young (International Journal of Sports Physical Therapy, 2023)
# Background